2016
DOI: 10.1038/srep28608
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory cytokines and ERK1/2 signaling in chronic prostatitis/chronic pelvic pain syndrome with related mental health disorders

Abstract: Mental health disorders(MHD) in chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) have been widely studied. However, the underlying role of inflammatory cytokines and their associated signaling pathways have not been investigated. Here, we report the potential role of cytokines and associated signaling pathways in CP/CPPS patients with MHD and in a CP/CPPS animal model. CP/CPPS patients (n = 810) and control subjects (n = 992) were enrolled in this case-control multicenter study, and serum cytokine le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 56 publications
3
38
0
1
Order By: Relevance
“…Quick et al had established the CP/CPPS rat model and found that MCP‐1 and MIP‐1a were up‐regulated in prostatic fluid, in addition, they also confirmed that these two chemokines were associated with chronic pain. On the other hand, IL‐1β and TNF‐α were the vital proinflammatory factors, which are confirmed in numerous studies to greatly affect the development of CP/CPPS . IL‐6 is a major immune factor in inflammatory response, which regulates IL‐2 production and down‐regulates the synthesis of IL‐1β and TNF‐a.…”
Section: Discussionmentioning
confidence: 85%
“…Quick et al had established the CP/CPPS rat model and found that MCP‐1 and MIP‐1a were up‐regulated in prostatic fluid, in addition, they also confirmed that these two chemokines were associated with chronic pain. On the other hand, IL‐1β and TNF‐α were the vital proinflammatory factors, which are confirmed in numerous studies to greatly affect the development of CP/CPPS . IL‐6 is a major immune factor in inflammatory response, which regulates IL‐2 production and down‐regulates the synthesis of IL‐1β and TNF‐a.…”
Section: Discussionmentioning
confidence: 85%
“…Inflammatory and autoimmune mechanism may play an important role in the development of cp/cpps. Several cytokines, including IL‐1α, IL‐1β, IL‐4, IL‐13 and TNF‐α, have been found apparently higher than control group both in the serum of CP/CPPS patients and CP/CPPS rat prostates(Hu et al., ). Inflammatory cells, such as T lymphocytes, B lymphocytes and macrophages, were detected in the prostatic massage fluid of cp/cpps patients in the absence of infections (Ludwig et al., ).These evidence indicate an ongoing autoimmune process and inflammation within the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Only in recent years, a few studies have examined the emotional effects of prostatitis in animal models. Hu et al 9 reported that EAP was closely associated with depressive‐like behavior, which was assessed by OFT. Consistent with this result, in this study, the exploratory behaviors in the OFT were more significantly reduced in the EAP group than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have advocated for the participation of hypothalamic‐pituitary‐adrenal axis dysfunction, pain, and personality changes in the CP/CPPS‐related mental disorders 7,8 . Also, prostate‐derived inflammatory cytokines that cross the blood‐brain barrier and further activate ERK1/2 signaling in several brain areas have been linked to the psychiatric symptoms in CP/CPPS 9 . However, up to date, the exact mechanisms underlying the association between CP/CPPS and depression are still unclear.…”
Section: Introductionmentioning
confidence: 99%